Pengembangan Sumber Daya Manusia Protokoler di Bagian Protokol Sekretariat Daerah Kota Cilegon - Zani, Elma; Ema Jumiati, Ipah; Stiawati, Titi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Human resources are one of the resources that most determine the success or failure of an organisation. Unlike other organisational resources, human resources are a factor of production that has a dominant influence on other factors of production. Every company or organisation always wants its employees to have good performance. The method used is to use a qualitative approach that aims to explore and understand a central symptom. In this study, Human Resource Development in the Protocol Section of the Cilegon City Regional Secretariat has not run optimally. HR development still needs to be improved because based on data and interview results, it states that planning, education and training and employee management are still not effective, employees are rarely included in education and training, seminars related to the main duties and functions of protocol. Supporting factors for the development of Human Resources are the availability of adequate facilities and infrastructure such as operational vehicles and electronic goods supporting the activities of the Protocol Section, good teamwork and technological advances that make it easier for protocols to carry out their duties both in the office and in the field. While the inhibiting factors for the development of Human Resources are the minimum number of employees participating in education and training in the form of training and seminars on an ongoing basis for protocol employees, customs or habits of different people and the absence of good HR management and planning in accordance with the Main Duties and Functions of the Protocol Section.